Tap the sap – investigation of latex-bearing plants in the search of potential anticancer biopharmaceuticals - Mazur, Oliwia; Bałdysz, Sophia; Warowicka, Alicja; Nawrot, Robert (Frontiers in Plant Science, 2022)
Latex-bearing plants have been in the research spotlight for the past couple of decades. Since ancient times their extracts have been used in folk medicine to treat various illnesses. Currently they serve as promising candidates for cancer treatment. Up to date there have been several in vitro and in vivo studies related to the topic of cytotoxicity and anticancer activity of extracts from latex-bearing plants towards various cell types. The number of clinical studies still remains scarce, however, over the years the number is systematically increasing. To the best of our knowledge, the scientific community is still lacking in a recent review summarizing the research on the topic of cytotoxicity and anticancer activity of latex-bearing plant extracts. Therefore, the aim of this paper is to review the current knowledge on in vitro and in vivo studies, which focus on the cytotoxicity and anticancer activities of latex-bearing plants. The vast majority of the studies are in vitro, however, the interest in this topic has resulted in the substantial growth of the number of in vivo studies, leading to a promising number of plant species whose latex can potentially be tested in clinical trials. The paper is divided into sections, each of them focuses on specific latex-bearing plant family representatives and their potential anticancer activity, which in some instances is comparable to that induced by commonly used therapeutics currently available on the market. The cytotoxic effect of the plant’s crude latex, its fractions or isolated compounds, is analyzed, along with a study of cell apoptosis, chromatin condensation, DNA damage, changes in gene regulation and morphology changes, which can be observed in cell post plant extract addition. The in vivo studies go beyond the molecular level by showing significant reduction of the tumor growth and volume in animal models. Additionally, we present data regarding plant-mediated biosynthesis of nanoparticles, which is regarded as a new branch in plant latex research. It is solely based on the green-synthesis approach, which presents an interesting alternative to chemical-based nanoparticle synthesis. We have analyzed the cytotoxic effect of these particles on cells. Data regarding the cytotoxicity of such particles raises their potential to be involved in the design of novel cancer therapies, which further underlines the significance of latex-bearing plants in biotechnology. Throughout the course of this review, we concluded that plant latex is a rich source of many compounds, which can be further investigated and applied in the design of anticancer pharmaceuticals. The molecules, to which this cytotoxic effect can be attributed, include alkaloids, flavonoids, tannins, terpenoids, proteases, nucleases and many novel compounds, which still remain to be characterized. They have been studied extensively in both in vitro and in vivo studies, which provide an excellent starting point for their rapid transfer to clinical studies in the near future. The comprehensive study of molecules from latex-bearing plants can result in finding a promising alternative to several pharmaceuticals on the market and help unravel the molecular mode of action of latex-based preparations.